Calixthe Beyala: black face(s) on French TV - Hitchcott, Nicki (Taylor & Francis, 2004)
As president and spokeswoman of the French black rights movement, Collectif Egalité, Cameroonian-born novelist Calixthe Beyala is committed to pushing for an improvement in the representation of black people on television in France. This article discusses the ways in which the Collectif has attempted to draw the French public's attention to the lack of 'visible minorities' on French TV. It takes as a test case the controversial figure of Beyala herself who has become something of a minor TV celebrity in her own right. What emerges as an apparent contradiction between Beyala's own media representation and the Collectif's campaign will serve to illustrate the ambivalent positioning of black citizens in contemporary France.